2013
DOI: 10.15625/0866-7160/v34n4.2688
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of nitrate concentration and illumination conditions on the growth of microalga Haematococcus pluvialis

Abstract: Viện Công nghệ sinh học, *ddhong60vn@yahoo.com TÓM TẮT: Vi tảo lục Haematococcus pluvialis được biết đến rộng rãi như là nguồn cung cấp astaxanthin tự nhiên. Nhiều vi sinh vật như nấm, địa y, vi khuẩn, vi tảo khác cũng có khả năng tổng hợp astaxanthin nhưng hàm lượng astaxanthin ở H. pluvialis được xem là cao nhất. Trong bài báo này, chúng tôi nghiên cứu ảnh hưởng kết hợp của nồng độ nitrate và chế độ chiếu sáng lên sinh trưởng của vi tảo H. pluvialis khi nuôi ở bình nhựa thể tích 10 lít. Kết quả nghiên cứu ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Calculation of the Péclet number for each condition (Figure ) showed that selecting a flow rate of 1 L/min provided the necessary CO 2 transfer while sustaining good axial liquid mixing. This is equivalent to 1 vvm, which is commonly used in airlift photobioreactors . Keeping the flow rate and temperature constant at 1 L/min and 33 °C will allow for a reduced number of runs and greater focus on the effects of light intensity and inlet CO 2 concentration on the growth of Synechococcus PCC7942.…”
Section: Resultsmentioning
confidence: 99%
“…Calculation of the Péclet number for each condition (Figure ) showed that selecting a flow rate of 1 L/min provided the necessary CO 2 transfer while sustaining good axial liquid mixing. This is equivalent to 1 vvm, which is commonly used in airlift photobioreactors . Keeping the flow rate and temperature constant at 1 L/min and 33 °C will allow for a reduced number of runs and greater focus on the effects of light intensity and inlet CO 2 concentration on the growth of Synechococcus PCC7942.…”
Section: Resultsmentioning
confidence: 99%